Microstructural analysis of shearband boudin - preliminary results - Rodrigues, Benedito C. (2011)
The internal structure of a shearband boudin resulting from an original igneous, hydrothermal or metamorphic segregation tabular rigid body is a subject of scientific interest. It allows understanding the deformation mechanisms acting on homogeneous quartz aggregate activated during simple shear progressive deformation. This communication is focused on the characterization of two main structural aspects: (i) the existence of different internal domains in shearband boudins; (ii) the development of internal structures related with its genesis and evolution, namely, secondary shear planes c’ type-I and c’ type-II, parameter B-t (mass accumulation sector on blunt tip of shearband boudin) and S-t (sharp tip of shearband boudin), internal migration of mass (rotation and translation) and mechanisms of ductile deformation activated on the process.